Support for smoke-free public places among adults in four countries in sub-Saharan Africa. Issue 12 (12th January 2020) - Mamudu, Hadii M; Owusu, Daniel; Asare, Bossman; Williams, Faustine; Asare, Matthew; Oke, Adekunle; Poole, Amy; Osedeme, Fenose; Ouma, Ogwell A E
Abstract: Introduction: There is no known safe level of secondhand smoke exposure; yet, less than 30% of the global population is covered by comprehensive smoke-free policies as of 2016 and there are few smoke-free policies in sub-Saharan Africa (SSA). This study examines the support for smoke-free public places in SSA and delineates their correlates. Methods: Data collected through the Global Adult Tobacco Survey (2012–2017) were analyzed using SAS for descriptive and multivariable analyses, with a significance level set at p < .05. Results: No SSA country had comprehensive smoke-free policies, defined as a prohibition of smoking in eight public places. In the four countries whose Global Adult Tobacco Survey data were analyzed (Nigeria, Cameroon, Kenya, and Uganda), support for the prohibition of smoking in public places was over 90% in all eight public places except bars. Support for smoking prohibition in bars was 65.8%, 81.1%, 81.4%, and 91.0% in Nigeria, Cameroon, Kenya, and Uganda, respectively. Factors associated with support for smoke-free bars differed across the four countries, but in all countries, current smokers had decreased odds of support for smoke-free bars. Knowledge of secondhand smoke harm and living in smoke-free homes were associated with increased odds of support for smoke-free bars in all countries except Kenya. Conclusion: The high support for smoke-free public places should inform the efforts of the public health community and policymakers in these four SSA countries toward meeting their obligations of Article 8 of the World Health Organization Framework Convention on Tobacco Control (WHO FCTC). Implications: Much of the population in SSA is not protected by comprehensive smoke-free policies. It was found that the overwhelming majority of adults in four large countries in SSA support the prohibition of smoking in public places and that knowledge of the health dangers of smoking and exposure to secondhand smoke and home smoking rules increased support for the prohibition. High support for the prohibition of smoking in these four SSA countries suggests tobacco control proponents should advocate for comprehensive smoke-free policies.